The level of transformational leadership and the effectiveness of primary school organization - Noraziah Mamat; Mohd Faiz Mohd Yaakob; Wiwik Wijayanti (Jurnal Akuntabilitas Manajemen Pendidikan, 2021)
The purpose of this quantitative survey type study was to find out the effectiveness of transformational leadership practices in primary school organization in Kota Bharu District, Kelantan, Malaysia.Â  Data were collected from 244 teachers randomly selected from 11 daily primary schools. The measurement tool used was the â€œTransformational Leadership Inventorsâ€ (TLI) which contained 22 items related to the six dimensions of transformational leadership developed by Podsakoff, McKenzie and Boomer (1996). For organizational effectiveness, the Effectiveness International School Questionnaire (EISQ) by Doran (2004) which contained 55 items with 11 dimensions was used. The IBM Statistical Package for Social Sciences version 26.0 (IBM SPSS 26.0) was used to analyze the data. Overall, the results of the study showed that transformational leadership practices were at a very high level (mean = 4.32 and SD = 0.503). As for organizational effectiveness, the results showed that organizational effectiveness was at a high level (mean = 3.92 and SD = 0.430). Overall, this research has achieved the set goals.